A matlab-based low-cost autopilot for autonomous helicopter development - Ismaila B., Tijani; Akmeliawati, Rini; Legowo, Ari; Tun Muzamil, L. A. (2012)
The challenges associated with the software and hardware integration activities in development of flight autopilot system for autonomous helicopter have called for a change of tactics. The resulting effect is for example, a long time delay in autopilot system design, testing and deployment coupled with the fact that several other autonomous helicopter development tasks depend largely on availability of the autopilot system. Though, the use of off-the-shelf autopilot for a flight control system may ease these challenges, they are generally characterized with limited functionalities, and restrict the user’s design authority. As alternative approach, this paper presents the development of a MATLAB-based autopilot system for autonomous helicopter development. This approach provides an integrated design environment for rapid-prototyping of a low-cost autopilot system. The results of real-time application of the autopilot for flight data logging are presented. The performance shows the effectiveness of the developed autopilot system in small scale autonomous helicopter design and implementation. This is hope to reduce the design cycle time involves in the deployment of small scale autonomous helicopter in various civil low-cost, small payload applications.